Perovskite La1−xKxCoO3−δ (0 ≤ x ≤ 0.5): a novel bifunctional OER/ORR electrocatalyst and supercapacitive charge storage electrode in a neutral Na2SO4 electrolyte - Mondal R.; Mishra N.K.; Singh M.; Gupta A.; Singh P. (My University, 2025)
The as-prepared La1−xKxCoO3−δ (0 ≤ x ≤ 0.5) showed superior pseudocapacitive charge storage capacity in a neutral 0.5 M Na2SO4 electrolyte and superior electrocatalytic activities for the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) in a 1 M KOH electrolyte. 30% K doped p-type La0.7K0.3CoO3−δ presents superior OER activity with an overpotential of ∼335 mV at 10 mA cm−2 current rate in a 1 M KOH electrolyte. Additionally, La1−xKxCoO3−δ (0 ≤ x ≤ 0.5) presents an excellent charge-storage capacitance in a neutral 0.5 M Na2SO4 electrolyte resulting in a gravimetric capacitance of the La0.5K0.5CoO3−δ electrode equivalent to 378 F g−1, 282 F g−1, 221 F g−1, 163 F g−1, and 74 F g−1 at a current density of 1 A g−1, 2 A g−1, 3 A g−1, 5 A g−1, and 10 A g−1, respectively. After 2500 continuous cycles of charge/discharge, the La0.5K0.5CoO3−δ//AC cell exhibits higher stability, capacitive retention (94%) and coulombic efficiency (97%). The gravimetric charge storage capacity of ASCs (La0.5K0.5CoO3−δ//AC) in the full cell mode showed capacitance equivalent to 308 F g−1, 287 F g−1, 238 F g−1, 209 F g−1 and 162 F g−1 at current densities of 1 A g−1, 2 A g−1, 3 A g−1, 5 A g−1 and 10 A g−1 in a neutral 0.5 M Na2SO4 electrolyte respectively. Maximum specific power equivalent to ∼6884 W kg−1 was observed at a current density of 10 A g−1 when the specific energy reached ∼57 W h kg−1 for the full cell. The double exchange mechanism coupled with stoichiometric oxygen defects present in the perovskite lattice seems to be operative behind the enhanced electrocatalytic OER properties, and additionally, it improves the charge storage kinetics of the La1−xKxCoO3−δ (0 ≤ x ≤ 0.5) electrode in a neutral Na2SO4 electrolyte for supercapacitor application. This work presents a rational strategy for introducing facile oxygen ion defects into perovskite structured La1−xKxCoO3−δ (0 ≤ x ≤ 0.5) to develop multifunctional electrode materials for a supercapacitor and energy conversion (OER/ORR) electrode of metal-air batteries. © 2022 The Royal Society of Chemistry.